The illusion of untranslatability: a theoretical perspective with reference to the translation of culture-bound euphemistic expressions in the Qur'an - Al-Saidi, A. Ali H.; Md Rashid, Sabariah (Australian International Academic Centre, 2016)
The present study investigates the notion of untranslatability where the concept of equivalence is reconsidered since the misconceptions, related to the said concept, inevitably lead to the emergence of untranslatability. Identifying equivalence as relative, approximate and necessary identity makes the notion of untranslatability a mere theorization. The objectives of the present study are (1) to investigate the notion of untranslatability in terms of the misconceptions associated with the concept of equivalence (2) to examine the possibility of translatability from Arabic into English focusing on culture-bound euphemistic expressions in the Quran as an area of challenge in translation. Data on the translation of culture-bound euphemistic expressions were purposively selected from the Quran and its four identified English translations. Ten examples were randomly selected and the criterion for their selection is that they are culture-bound and therefore translation-resistant. Qualitative content analysis was used to examine the source data by referring to traditional exegetical books to determine the source text intentionality. Additionally, the translated data were analyzed according to the functional equivalence proposed by Nida (1993; 2001).Findings of this study revealed that translatability is always possible and, accordingly, untranslatability is no more valid.